A review of yeast-derived emulsifiers developed through microbial fermentation for the food sector - Shokri, Sajad; Hashemi, Zahrasadat; Hassan, Sona Ayadi; Chuck, Christopher J. (Frontiers in Microbiology, 2026)
Microbial fermentation is an established technology that is becoming increasingly used to produce key food components. Among the various microorganisms used, yeasts play crucial roles due to their efficiency in synthesizing a wide range of industrially important compounds. The growing demand for sustainable, locally sourced, and animal-free food ingredients has increased the focus on yeast biomass and its derivatives. These yeast-based products, such as food emulsifiers, are a promising next-generation of food components, offering advantages like a low risk of allergenicity. Yeast biomass-based fractions have been effectively used as emulsifiers in various food products including in dairy, meat, bakery, meat alternatives, mayonnaises and salad dressing, with effective properties demonstrated in a range of oil-in-water, water-in-oil, and Pickering emulsion models. Both whole cell biomass and yeast cell fractions such as the yeast cell wall, mannoproteins, glucans, exopolysaccharides and other yeast-derived compounds have been demonstrated to function as effective emulsifiers. An increasingly large number of yeasts, beyond just Saccharomyces cerevisiae, have been studied as potential sources of these emulsifiers with the extraction and purification methods employed depending on the specific emulsifier targeted, the required purity, and the intended application. Efficient, cost-effective, and sustainable processes are key to enabling industrial-scale production of these emulsifiers, as such this article reviews the potential yeast-derived food emulsifiers, lists the various yeast species investigated to date, examines the extraction and purification methods, and highlights the potential food applications of these yeast-derived emulsifiers.